1993
DOI: 10.1152/ajpendo.1993.265.5.e752
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate dehydrogenase activity and acetyl group accumulation during exercise after different diets

Abstract: Pyruvate dehydrogenase activity (PDHa) and acetyl group accumulation were examined in human skeletal muscle at rest and during exercise after different diets. Five males cycled at 75% of maximal O2 uptake (VO2 max) to exhaustion after consuming a low-carbohydrate diet (LCD) for 3 days and again 1-2 wk later for the same duration after consuming a high-carbohydrate diet (HCD) for 3 days. Resting PDHa was lower after a LCD (0.20 +/- 0.04 vs. 0.69 +/- 0.05 mmol.min-1.kg wet wt-1; P < 0.05) and coincided with a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
163
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(184 citation statements)
references
References 28 publications
18
163
1
1
Order By: Relevance
“…AcCoA, acetyl-CoA; MaCoA, malonyl-CoA; FACoA, fatty acyl-CoA; CAT, carnitine acetyltransferase; CPT, carnitine palmitoyltransferase-1/2 system; AMPK, 5Ј-AMP-activated protein kinase; CL, citrate lyase; ϩ, activating effect; Ϭ, inhibiting effect. muscle carnitine content and fat oxidation rate were markedly higher with low muscle glycogen (25). Taken together, the present and previous studies suggest a relation between muscle free carnitine availability and fat oxidation rate in human skeletal muscle during exercise.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…AcCoA, acetyl-CoA; MaCoA, malonyl-CoA; FACoA, fatty acyl-CoA; CAT, carnitine acetyltransferase; CPT, carnitine palmitoyltransferase-1/2 system; AMPK, 5Ј-AMP-activated protein kinase; CL, citrate lyase; ϩ, activating effect; Ϭ, inhibiting effect. muscle carnitine content and fat oxidation rate were markedly higher with low muscle glycogen (25). Taken together, the present and previous studies suggest a relation between muscle free carnitine availability and fat oxidation rate in human skeletal muscle during exercise.…”
Section: Discussionsupporting
confidence: 84%
“…The combination of unchanged free carnitine content and reduced malonyl-CoA content leads to a marked increase in fat oxidation rate from rest to exercise. Muscle concentration of pyruvate was not measured in the present study but was previously shown to increase more from rest to exercise with high than with low muscle glycogen (25). The muscle concentration of citrate, the source of the acetyl-CoA from which malonyl-CoA is generated (35), was not measured in the present study but was previously shown not to differ during exercise with high and low muscle glycogen, although an increase with exercise occurred (11).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Many models have been used to perturb this partitioning, such as starvation (12,17,26,36), and a high-fat diet (27,28,30). One such perturbation previously used has been endurance training (17,19,20), which in general causes a shift toward increased fat oxidation and decreased carbohydrate utilization.…”
mentioning
confidence: 99%
“…It has been found that in states of restricted carbohydrate availability there is an increase in skeletal muscle PDK activity (5,6,26,27,28) and PDK4 protein content (26,27,36), while similar nutritional states also cause a decrease in PDP2 protein content in rat heart and kidney (12) and skeletal muscle, with this decrease leading to a decrease in PDP activity (17). As a result of these adaptations there is an overall decrease in the active form of PDH (PDHa; 6,28,30), allowing for the conservation of carbohydrates, which is essential during these carbohydratedeficient perturbations.…”
mentioning
confidence: 99%